1993
DOI: 10.1002/neu.480241103
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of early postnatal development of cortical neurons that proceed independently of normally present extrinsic influences

Abstract: To examine the contribution of local versus extrinsic influences on postnatal development of cortical neurons, we compared the maturation of deep (infragranular) layer neurons in isolated slices of neocortex grown in organotypic culture to a similar population of neurons developing in vivo. All slice cultures were prepared from sensorimotor cortices of newborn mice (P0) and neurons in these cultures were examined at daily intervals during the first 9 days in vitro (DIV). The maturational state of neurons devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 50 publications
5
13
0
Order By: Relevance
“…Previous studies have shown that neuronal migration, layer formation, cellular morphology, and physiology develop normally in cultured cortical explants (Yamamoto et al, 1989(Yamamoto et al, , 1992Bolz et al, 1990Molnar and Blakemore, 1991;Gotz and Bolz, 1992;Annis et al, 1993;Dantzker and Callaway, 1998). Similarly, individually YFP-labeled cells in our slice cultures exhibited a projection pattern and branch formation that is typical for layer 2/3 cells in rodents (Lohmann and Rorig, 1994;van Brederode et al, 2000).…”
Section: Comparison Of Axons Of Upper Layer Neurons In Organotypic Slsupporting
confidence: 78%
“…Previous studies have shown that neuronal migration, layer formation, cellular morphology, and physiology develop normally in cultured cortical explants (Yamamoto et al, 1989(Yamamoto et al, , 1992Bolz et al, 1990Molnar and Blakemore, 1991;Gotz and Bolz, 1992;Annis et al, 1993;Dantzker and Callaway, 1998). Similarly, individually YFP-labeled cells in our slice cultures exhibited a projection pattern and branch formation that is typical for layer 2/3 cells in rodents (Lohmann and Rorig, 1994;van Brederode et al, 2000).…”
Section: Comparison Of Axons Of Upper Layer Neurons In Organotypic Slsupporting
confidence: 78%
“…Although not specifically addressed in this study, the increase in excitation is mostly likely produced by a number of different mechanisms acting in parallel. Indeed, increases in excitatory synaptic strength, spine density, and dendritic and axonal branching have all been reported in organotypic slices as a function of age (Caeser et al, 1989;Annis et al, 1993;Yamada et al, 2000;De Simoni et al, 2003;Uesaka et al, 2005). All or a subset of these mechanisms could underlie the increase in evoked activity reported here.…”
Section: Development and Mechanisms Underlying Spontaneous Activity Isupporting
confidence: 56%
“…The postnatal neurons gain the capacity to fire repetitive trains of AP (Annis et al 1993;Heidi et al 2003). But in our results, most of the neurons in P B 6 group (n = 8) were not able to emit a typical action potential waveform which was in accordance with that in embryonic 13 (E13) of rat spinal motoneuron reported by Gao and ZIiskind-Conhaim (1998) (Fig.…”
Section: Developmental Changes Of Action Potentials In Rats' Corticalmentioning
confidence: 97%